Monitoring Jumlah Orang di Ruangan Menggunakan Teknologi IOT - Nurlaili, Dewi; Maulindar, Joni; Hartanti, Dwi (Universitas Multi Data Palembang, 2025)
The problem addressed in this research is the need to monitor the number of people entering and exiting a meeting room automatically and accurately. The objective of this study is to develop a system for monitoring the number of people in a meeting room using IoT technology to improve the efficiency of room capacity management. The method used in this research involves the application of an Arduino Uno microcontroller with HC-SR04 ultrasonic sensors to detect object movement and display the results on an LCD in real-time. The test results show that the system successfully detects the number of objects entering and exiting the room accurately. The LCD display shows numbers corresponding to the changes in the number of people inside the room with labels